2009 Fifth International Conference on Wireless Communication and Sensor Networks (WCSN) 2009
DOI: 10.1109/wcsn.2009.5434786
|View full text |Cite
|
Sign up to set email alerts
|

Double Pole Four Throw switch design with CMOS inverter

Abstract: To avoid the uses of multiple RF chain associated with the multiple antennas, RF switch is most essential component. Multiple antennas systems are used to replace traditional single antennas circuitry in the radio transceiver system in order to improve the transmission capability and reliability. The desired switching system must have low cost and simple structure, yet still can capture all the advantage of Multiple Inputs Multiple Output (MIMO) systems. In this paper, we have proposed a Double Pole Four Throw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…1(a). In this paper, we have extend our recently reported work [15] and proposed a DP4T switch design and replace the CMOS inverter property with DP4T RF switches, by using DG CMOS for 45-nm technology. This design of double-gate transistors resolves the problem of short channel effect that occurs in MOSFET structures.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…1(a). In this paper, we have extend our recently reported work [15] and proposed a DP4T switch design and replace the CMOS inverter property with DP4T RF switches, by using DG CMOS for 45-nm technology. This design of double-gate transistors resolves the problem of short channel effect that occurs in MOSFET structures.…”
mentioning
confidence: 70%
“…Note that the minimal change in element characteristics over 0 to 5 V range, validating the use of these devices at lower control voltages. For this purpose at 0.8-µm technology DP4T DG RF CMOS switch design we compare L = 0.8 µm and W = 400 µm with the L = 2.0 µm and W = 4000 µm (aspect ratio is 500 and 2000 respectively) and for 45-nm technology switch design we compare L = 0.045 µm, W = 22.5 µm, with L = 0.045 µm, W = 90 µm (where aspect ratio is 500 and 2000 respectively same as before), here we discussed the attenuation, which is found that at lower size, attenuation is lower [15,[33][34][35][36]. Attenuation measurements were performed on the 0.8-µm and 45-nm technology by varying the gate control voltage (V CT L ) over a 0 to 1.2 volt range.…”
Section: Attenuation ('On' Switch Resistance)mentioning
confidence: 99%
See 1 more Smart Citation
“…We can experiment with program flow and data processing with only LCR meter and VEE programming. VEE provides an Instrument Manager and a Dynamic input/output (I/O) server to simplify the tasks of discovering, configuring, and managing external instruments [8][9][10]. The VEE supports several types of instrument drivers.…”
Section: Introductionmentioning
confidence: 99%
“…In the design of DP4T DG RF CMOS switch structures with 45-nm technology for digital and analog, a transaction between speed and frequency response and circuit complexity is always encountered. The properties for RF CMOS switch design for the application in communication and designed results are presented and have been designed to optimize for the particular application [14]. A DP4T DG RF CMOS switch has the properties as fixed tuned matching networks, low quality factor matching networks, high power output, mounting flange packages, and silicon grease.…”
Section: Introductionmentioning
confidence: 99%